Konsep Profesi Keguruan MI - Maksum, Khanif (Universitas Alma Ata, 2013)
The Professional work which requires some sciences, it be learned and then applied to the public interest. Based on the requiring above, this professional job is different from other jobs where a profession requiring the specialized skills and expertise in carrying out his/her profession. Teacher is a professional work, and as a professional work, it must meet certain qualifications. Therefore, it needs many requirements, ig a good motivation, knowledge and skills, dedication, ethics, and entitled to a reward. The professional work involves intellectual activity, distinct body knowledge, and requires long preparation to do, continue service training, a career and a life of permanent membership, behavior, concerned deal with service, having professional organizations, and adherent code of conduct by members. Keywords: Professionalism